Sexually Transmitted Infection Testing in the National Veterans Health Administration Patient Cohort During the Coronavirus Disease 2019 Pandemic. (23rd August 2022) - Beste, Lauren A; Keddem, Shimrit; Borgerding, Joleen; Lowy, Elliott; Gardella, Carolyn; McFarland, Lorenzo; Comstock, Emily; Fonseca, Giuseppe Allan; Van Epps, Puja; Ohl, Michael; Hauser, Ronald G; Ross, David; et al.
Abstract: Background: We performed a retrospective study of chlamydia, gonorrhea, syphilis, and human immunodeficiency virus (HIV) testing in the Veterans Health Administration (VHA) during 2019–2021. Methods: We determined the annual number of chlamydia, gonorrhea, syphilis, and HIV tests from 2019 through 2021 using electronic health record data. We calculated rates by age, birth sex, race, census region, rurality, HIV status, and use of preexposure prophylaxis. Results: The VHA system experienced a 24% drop in chlamydia/gonorrhea testing, a 25% drop in syphilis testing, and a 29% drop in HIV testing in 2020 versus 2019. By the conclusion of 2021, testing rates had recovered to 90% of baseline for chlamydia/gonorrhea, 91% for syphilis, and 88% for HIV. Declines and subsequent improvements in sexually transmitted infection (STI) testing occurred unequally across age, sex, race, and geographic groups. Testing for all 4 STIs in 2021 remained below baseline in rural Veterans. Excluding those aged <25 years, women experienced a steeper decline and slower recovery in chlamydia/gonorrhea testing relative to men, but quicker recovery in HIV testing. Asian Americans and Hawaiian/Pacific Islanders had a steeper decline and a slower recovery in testing for chlamydia/gonorrhea. Black and White Veterans had slower recovery in HIV testing compared with other race groups. People living with HIV experienced a smaller drop in testing for syphilis compared with people without HIV, followed by a near-total recovery of testing by 2021. Conclusions: After dramatic reductions from 2019 to 2020, STI testing rates returned to near-baseline in 2021. Testing recovery lagged in rural, female, Asian American, Hawaiian/Pacific Islander, and Black Veterans. Abstract : The Veterans Affairs system experienced a drop of 24%, 25%, and 29% in chlamydia/gonorrhea, syphilis, and HIV testing, respectively, in 2020 versus 2019. Initial declines and subsequent improvements in sexually transmitted infection testing occurred unequally across age, sex, race, and geographic groups.